Targeted Disruption of Fibronectin-Integrin Interactions in Human Gingival Fibroblasts by the RI Protease of Porphyromonas gingivalis W50 - Scragg, M. A. (American Society for Microbiology, 1999)
Cell surface integrins mediate interactions between cells and their extracellular matrix and are frequently exploited by a range of bacterial pathogens to facilitate adherence and/or invasion. In this study we examined the effects of Porphyromonas gingivalis proteases on human gingival fibroblast (HGF) integrins and their fibronectin matrix. Culture supernatant from the virulent strain W50 caused considerably greater loss of the β(1) integrin subunit from HGF in vitro than did that of the beige-pigmented strain W50/BE1. Prior treatment of the W50 culture supernatant with the protease inhibitor Nα-p-tosyl-l-lysine chloromethyl ketone (TLCK) blocked its effects on cultured cells, indicating that this process is proteolytically mediated. Purified arginine-specific proteases from P. gingivalis W50 were able to mimic the effects of the whole-culture supernatant on loss of β(1) integrin expression. However purified RI, an α/β heterodimer in which the catalytic chain is associated with an adhesin chain, was 12 times more active than RIA, the catalytic monomer, in causing loss of the α(5)β(1) integrin (fibronectin receptor) from HGF. No effect was observed on the α(V)β(3) integrin (vitronectin receptor). The sites of action of RI and RIA were investigated in cells exposed to proteases pretreated with TLCK to inactivate the catalytic component. Use of both monoclonal antibody 1A1, which recognizes only the adhesin chain of RI, and a rabbit antibody against P. gingivalis whole cells indicated localization of RI on the fibroblasts in a clear, linear pattern typical of that seen with fibronectin and α(5)β(1) integrin. Exact colocalization of RI with fibronectin and its α(5)β(1) receptor was confirmed by double labeling and multiple-exposure photomicroscopy. In contrast, RIA bound to fibroblasts in a weak, patchy manner, showing only fine linear or granular staining. It is concluded that the adhesin component of RI targets the P. gingivalis arginine-protease to sites of fibronectin deposition on HGF, contributing to the rapid loss of both fibronectin and its main α(5)β(1) integrin receptor. Given the importance of integrin-ligand interactions in fibroblast function, their targeted disruption by RI may represent a novel mechanism of damage in periodontal disease.